Photodynamic therapy against oesophageal cancer : In vitro testing of potential new agents - Vaz, Gisela (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
Oesophageal malignancies are one of the leading causes of death in the Western World. The incidence of these diseases is currently on the rise alternative but powerful therapies are being developed against them, an example of these is photodynamic therapy (PDT) which is an emerging treatment against oesophageal cancer. However, it is still a long way from being widely used as an alternative to the more conventional therapies. The most commonly used photosensitisers are based on porphyrins and their derivatives yet those in clinical use still show many side effects and issues such as prolonged patient phototoxicity.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin